Exploring evidence of healthcare-seeking pathways for maternal complications in Sub-Saharan Africa: a scoping review - Alehegn Bishaw Geremew; Claire T. Roberts; Bekalu Getnet Kassa; Shahid Ullah; Jacqueline H. Stephens (BMC Pregnancy and Childbirth)
Abstract Background Maternal mortality in Sub-Saharan Africa (SSA) accounted for 70% of global maternal deaths in 2020. Delay/failure in care-seeking is linked with a high proportion of maternal deaths. However, evidence is limited on how women and families recognise complications and decide to seek care for complications. In this scoping review, we examined evidence of the recognition of maternal complications, decision-making, and care-seeking during maternal complications from women, families, and community perspectives in SSA. Methods A scoping review was conducted following Joanna Briggs Institute guidelines. We report findings using Preferred Reporting Items for Systematic Review and Meta-Analysis scoping review extension checklist. We searched five electronic databases (Medline, Scopus, Web of Science, ProQuest, Emcare) and Google Scholar and included studies published in English between 2016 and 2024. A qualitative content analysis was undertaken. Results Of 16,777 articles identified, 46 were included (29 qualitative, 11 quantitative, and six mixed methods). About half the studies (52%) were from eastern SSA, and 30.4% were from western SSA. Few studies (10.9%) were from Southern SSA, and just one was from central SSA. Seventeen studies discussed at least some form of care-seeking pathway. Frequently, women did not recognise the symptoms and severity of complications, and others (mothers-in-law/mother, partners, and traditional birth attendants (TBA)) were involved. TBAs were widely involved in illness recognition but failed to recognise the severity of complications. Partners were the primary decision-makers in seeking care, and TBA and mothers-in-law were also frequently involved, while women were less involved. Most women initially sought care from informal sources of care and visited health facilities after using informal sources. Financial issues, transportation, distance, perceived causes of supernatural, fear of caesarean section, cultural norms, and trust in TBA care were barriers, while knowledge of complications, women’s decision-making, social support, lived experience/witnessing others, antenatal care, and user-free health services were enablers to seek care from health facilities. Conclusions This study highlights the complex care-seeking pathway during maternal complications and the need for further research focusing explicitly on each care-seeking process. Efforts to reduce identified barriers and maximise enablers may improve timely and appropriate care-seeking.